Operational Efficiency of BTPN Syariah During the Covid-19 Pandemic: A Data Envelopment Analysis Approach - Radithya Dzaky Waradana (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2026)
This study analyzes the operational efficiency of BTPN Syariah (2019-2023), a bank focusing on the productive low-income women segment. Amidst the COVID-19 pandemic, the bank faced a